Insect fat influences broiler performance, meat quality, and the cecal microbiota similarly to plant oils rather than animal fats - Muhammad Rumman Aslam; Bartosz Kierończyk; Mateusz Rawski; Piotr Szymkowiak; Kinga Stuper-Szablewska; Paweł Kołodziejski; Robert Mikuła; Agata Dankowiakowska; Damian Józefiak (Scientific Reports)
Abstract We evaluated the addition of Hermetia illucens larvae (BSFL) fat to broiler diets compared to that of soybean oil (SO), rapeseed oil (RO), palm oil (PO), palm kernel fatty acid distillate (PKFD), poultry fat (PF), pig lard (PL), and beef tallow (BT) on performance, meat quality, and cecal microbiota abundance. BSFL addition reduced the feed conversion ratio compared to PO, PF, and BT addition and improved nutrient digestibility at 14 days and 28 days of age. BSFL addition enhanced broiler immune responses compared with SO, PO, and PL by increasing IgA levels; compared to PO by increasing IgG levels; and compared to PL by increasing IgY and IL-6 levels. Moreover, broiler free triiodothyronine levels increased when BSFL was added. Reduced drip loss after 7 days was observed in the RO, PO, PF, PL, and BT groups, while the salt-induced water uptake in the PL group was greater than that in the BSFL group. Compared with the SO group, BSFL addition increased C18:3 and overall n-3 FAs in breast meat. BSFL fat in broiler diets leads to outcomes that are more similar to those of plant oils than to those of animal fats, particularly regarding nutrient digestiblity and immune response.